1999
DOI: 10.1007/bf02475755
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of oleic acid over sol-gel ruthernium catalysts

Abstract: Abs~a~The hydrogenation of oleic acid to oleyl alcohol over Ru-alumina and Ru-Snalumina sol-gel catalysts has been studied. It was found that, besides its hydrogenation activity, the Ru-Sn-alumina catalyst promotes the cis-trans isomerization of the unsaturated acid. This effect is used to explain some kinetic features of the system, like the high induction time observed in the formation of alcohols, and to re-examine the role of tin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
0
12
0
2
Order By: Relevance
“…With reference to the latter, and depending on the desired quality of the final fatty alcohol (which usually tolerates a maximum of 1-5 ppm of aldehydes), it must have an additional stage of selective hydrogenation to eliminate these compounds. Other steps that normally are used at high production scales, is the distillation of fractions (C 6-10 , C 12-14 , C [16][17][18] ) or other technical fractionation suitable for separation by carbon atoms number. The hydrogenation of fatty acid methyl esters for the production of long chain fatty alcohols is a process with well established technology, which has remained virtually unchanged in the last decades.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With reference to the latter, and depending on the desired quality of the final fatty alcohol (which usually tolerates a maximum of 1-5 ppm of aldehydes), it must have an additional stage of selective hydrogenation to eliminate these compounds. Other steps that normally are used at high production scales, is the distillation of fractions (C 6-10 , C 12-14 , C [16][17][18] ) or other technical fractionation suitable for separation by carbon atoms number. The hydrogenation of fatty acid methyl esters for the production of long chain fatty alcohols is a process with well established technology, which has remained virtually unchanged in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…Piccirilli et al 13 observed secondary reactions such as transesterification of oleyl alcohol with methyl oleate, leading to the formation of heavy esters. Costa et al 16 found that metals promote the cis-trans isomerization of unsaturated acids, as a side reaction. The effects of support and metal promoters on the selective hydrogenation of carbonyl group, in the case of the group VIII metal catalysts, are currently well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promotional effect of a second metal for the hydrogenation of esters exhibits not only in heterogeneous catalysis, but also in homogeneous catalysis. For example, after Re 2 (CO) 10 , Mo(CO) 6 and W(CO) 6 are added in Ru(acac) 3 and Ru 3 (CO) 12 respectively, the catalytic performance of Ru for the hydrogenation of esters is obviously improved [17] . Although the introduction of a second metal can greatly improve the catalytic performances of ruthenium-based catalysts, the hydrogenations are still performed at a temperature higher than 200 °C and a hydrogen pressure of 5.0 MPa, and the selectivity to the corresponding alcohol is generally lower than 80%.…”
Section: Introductionmentioning
confidence: 98%
“…Alcohols are generally obtained by hydrogenating aldehydes, ketones [1,2] , esters [3][4][5][6] . Because of the weak polarity and intrinsic steric hindrance of carboxylic group [7] , the hydrogenation of carboxylic acids and esters is very difficult.…”
Section: Introductionmentioning
confidence: 99%